Preparation method of layered oxide material sodium chromite of sodium-ion battery
The NACRO2 material is directly prepared through solid -phase oxidation reactions to solve the problem of the existing material's structural collapse and irreversible comparison capacity of existing materials. Provides high -performance positive electrode materials and sacrifice salt sodium supplements.
Patent Information
- Application Number
- CN202411585375.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-28
AI Technical Summary
The existing sodium ion battery material NaCrO2 has a large structural collapse and irreversible capacity at high voltages, and the side reactions of the electrode-electrolyte interface and ion migration limit the working voltage interval and energy density of the material, and the synthesis process is cumbersome and the energy consumption is high. High manufacturing cost.
By mixing the reduction sodium source and the hexavalent chromium source, the solid -phase oxidation reaction is used to prepare sodium chromate material, avoiding the burning process, simplifying the process and reducing energy consumption.
The NACRO2 material preparation with simple craftsmanship and excellent electrochemical performance has a high average voltage when the working voltage range is 2.2 to 3.6V, as the application of the positive electrode material; at 2.2 to 4.5V Up to 200mAh/G.
Smart Images

Figure CN119370888A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion battery materials, and specifically refers to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. Background Art
[0002] Power modules based on lithium-ion batteries have been the main driving force behind the explosive growth of portable electronic devices and the re-emergence of electric vehicles in the past 10 years. However, with the increasing demand for lithium-ion batteries, the problem of insufficient lithium resource reserves and rising lithium battery prices has been exposed, which also restricts the further large-scale application of energy storage devices. In contrast, sodium ranks fifth in abundance in the earth's crust, has abundant reserves and is cheap, so sodium-ion batteries are a more ideal large-scale energy storage battery system. Layered oxides are representative cathode material systems for sodium-ion batteries. The common NaCrO2 cathode material is a typical O3-type layered oxide cathode material with a high voltage platform and large discharge specific capacity; however, when charged to a higher potential, NaCrO2 causes structural collapse due to ion migration, resulting in a large irreversible specific capacity. Based on the above characteristics, NaCrO2 materials can be used as layered oxide cathode materials for sodium-ion batteries, and can also be used as sacrificial salt sodium supplements.
[0003] As a layered positive electrode oxide material, NaCrO2 material has side reactions at the electrode-electrolyte interface, which affects the material's cycle stability. On the other hand, ion migration under high voltage restricts the expansion of the material's operating voltage range and reduces the material's energy density.
[0004] NaCrO2 material as a sacrificial salt sodium supplement is an emerging research direction in recent years with the development of the commercialization process of sodium-ion batteries. It can provide additional active sodium ions and can provide additional active sodium ions for the polyanion positive electrode system. However, it is difficult for the sodium ions in the material to be completely removed, which restricts its sodium supplementation ability.
[0005] The synthesis process of NaCrO2 materials often uses a high-temperature calcination process. The process is cumbersome and energy-intensive, which increases the manufacturing cost. It is inconsistent with the low cost and mass production required for the use of sodium-ion batteries in large-scale energy storage, and hinders the commercialization of sodium-ion batteries. Summary of the invention
[0006] The invention aims to provide a method for preparing sodium chromite, a layered oxide material for sodium ion batteries, which has the characteristics of simple process and excellent electrochemical performance.
[0007] The present invention can be implemented by the following technical solutions:
[0008] The invention discloses a method for preparing sodium chromite, a layered oxide material for sodium ion batteries, comprising the following steps: using a reducing sodium source and a hexavalent chromium source as raw materials, directly mixing them and preparing them through a solid phase redox reaction.
[0009] Furthermore, the molar ratio of the reducing sodium source and the hexavalent chromium source is 0.8 to 1.2. Due to the chemical ratio of sodium and chromium in NaCrO2, the ratio of the sodium source to the chromium source should not be too different. Too much sodium source or too much chromium source will lead to the presence of impurities in the obtained material. Considering the volatilization of some raw materials during the calcination process, the preferred ratio is 0.8 to 1.2.
[0010] Furthermore, the solid-phase redox reaction mixture is one or more of high-energy ball milling, planetary ball milling, sand milling, and high-speed stirring and mixing of powders. Through collision and friction between solid particles, a redox reaction directly occurs at room temperature and pressure to achieve the generation of the target product.
[0011] Furthermore, the reducing sodium source is one or more of sodium citrate, sodium formate, sodium oxalate, sodium acetate, disodium ethylenediaminetetraacetate, sodium gluconate, and sodium hydride. The sodium source first provides the sodium ions required for the preparation of NaCrO2, and then the reducing sodium source is used as a reducing agent to undergo an oxidation-reduction reaction with a hexavalent chromium source, so that the high-valent chromium ions are reduced.
[0012] Furthermore, the hexavalent chromium source is one or more of chromium trioxide, chromium peroxide, and sodium chromate. The chromium source first provides the chromium ions required for preparing NaCrO2. Secondly, the hexavalent chromium source has strong oxidizing properties and undergoes redox reaction with the reducing sodium source to prepare the target product.
[0013] Furthermore, the tanks of ball mills, sand mills, and powder high-speed stirring and mixing equipment are equipped with pressure relief valves. Since the reducing sodium source is oxidized to produce gas during the redox reaction, the pressure relief valve is used to ensure that the interior of the tank is at normal pressure.
[0014] Furthermore, if the mixing method adopts ball milling, the ball-to-material ratio is 10-30 (mass ratio); if the mixing method adopts sand milling, the ball-to-material ratio is 3-8 (mass ratio, including solvent); ball milling and sand milling are to make the collision and friction between solid particles more complete. If the ball-to-material ratio is too high, the ball milling beads (sand milling beads) will occupy the space for material collision and friction; if the ball-to-material ratio is too low, the materials cannot fully collide and rub.
[0015] Furthermore, the solid phase redox reaction time should be 4 to 10 hours. The reducing sodium source and the high-valent oxidizing chromium source are used to prepare sodium chromite through solid phase redox reaction. Sufficient reaction time should be provided to ensure that the reaction proceeds fully. At the same time, too long reaction time will increase production costs. The preferred reaction time is 4 to 10 hours.
[0016] The present invention provides a method for preparing sodium chromite, a layered oxide material for sodium ion batteries, which has the following beneficial effects:
[0017] First, the preparation process is simple, using a hexavalent chromium source instead of a traditional trivalent chromium source, which is lower in cost. At the same time, the hexavalent chromium source is highly oxidizing, and the anion group of the sodium source is reducing. The NaCrO2 material can be directly prepared by redox reaction without going through a calcination process, and can be achieved only through a redox reaction between solid phase powders, which greatly reduces the energy consumption in the material preparation process.
[0018] Second, the electrochemical performance is excellent. The NaCrO2 material synthesized by this method can be used as a positive electrode material for sodium ion batteries when the working voltage range is 2.2 to 3.6V. It has a slope-type charge and discharge curve and a high average voltage of about 3.0V. When the working voltage range is 2.2 to 4.5V, it can be used as a sacrificial salt sodium supplement for sodium ion batteries, and the sodium supplement capacity can reach more than 200mAh / g.
[0019] Third, it has good processability. The NaCrO2 material is prepared based on the redox reaction and a reducing sodium source is used. The surface alkalinity of the NaCrO2 material will be reduced, which is beneficial to the subsequent preparation of slurry and electrode plates. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a flow chart of a method for preparing sodium chromite, a layered oxide material for sodium ion batteries;
[0021] Figure 2 The first week discharge curve of the sodium ion battery assembled with NaCrO2 material prepared in Example 1 as the positive electrode material;
[0022] Figure 3 Example 1: X-ray diffraction spectrum of NaCrO2 material obtained;
[0023] Figure 4 The first week discharge curve of the sodium ion battery assembled with NaCrO2 material prepared in Example 1 as sacrificial salt;
[0024] Figure 5 The first week discharge curve of the sodium ion battery prepared in Example 1 using the NaCrO2 material as sacrificial salt and NFPP composite and blank NFPP assembly;
[0025] Figure 6 The long cycle diagram of the sodium ion battery prepared in Example 1 using the NaCrO2 material as a sacrificial salt composited with NFPP and blank NFPP assembled. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.
[0027] The invention discloses a method for preparing sodium chromite, a layered oxide material for sodium ion batteries, comprising the following steps: using a reducing sodium source and a hexavalent chromium source as raw materials, directly mixing them and preparing them through a solid phase redox reaction.
[0028] Furthermore, the molar ratio of the reducing sodium source and the hexavalent chromium source is 0.8 to 1.2. Since the ratio of sodium to chromium in NaCrO2 is 1, the ratio of the sodium source to the chromium source should not be too different. Too much sodium source or too much chromium source will lead to the presence of impurities in the obtained material. Considering the volatilization of some raw materials during the calcination process, the preferred ratio is 0.8 to 1.2.
[0029] Furthermore, the solid-phase redox reaction mixing method includes but is not limited to ball milling, sand milling, high-speed stirring and mixing of powders, etc. Through the collision and friction between solid particles, the redox reaction directly occurs at room temperature and pressure to achieve the generation of the target product.
[0030] Furthermore, the reducing sodium source is one or more of sodium citrate, sodium formate, sodium oxalate, sodium acetate, disodium ethylenediaminetetraacetate, sodium gluconate, and sodium hydride. The sodium source first provides the sodium ions required for the preparation of NaCrO2, and then the reducing sodium source is used as a reducing agent to undergo an oxidation-reduction reaction with a hexavalent chromium source, so that the high-valent chromium ions are reduced.
[0031] Furthermore, the hexavalent chromium source is one or more of chromium trioxide, chromium peroxide, and sodium chromate. The chromium source first provides the chromium ions required for preparing NaCrO2. Secondly, the hexavalent chromium source has strong oxidizing properties and undergoes redox reaction with the reducing sodium source to prepare the target product.
[0032] Furthermore, the mixing equipment tank is provided with a pressure relief valve. During the redox reaction, the reducing sodium source is oxidized to produce gas, and the pressure relief valve is used to ensure that the interior of the tank is at normal pressure.
[0033] Furthermore, if the mixing method adopts ball milling, the ball-to-material ratio is 10-30 (mass ratio); if the mixing method adopts sand milling, the ball-to-material ratio is 3-8 (mass ratio, including solvent); ball milling and sand milling are to make the collision and friction between solid particles more complete. If the ball-to-material ratio is too high, the ball milling beads (sand milling beads) will occupy the space for material collision and friction; if the ball-to-material ratio is too low, the materials cannot fully collide and rub.
[0034] Example 1
[0035] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0036] 1. Weigh 0.03 mol sodium oxalate and 0.02 mol chromium trioxide;
[0037] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at a frequency of 50 Hz for 6 h to obtain NaCrO2 material;
[0038] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0039] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0040] Example 2
[0041] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0042] 1. Weigh 0.03 mol sodium oxalate and 0.02 mol sodium chromate;
[0043] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at a frequency of 50 Hz for 6 h to obtain NaCrO2 material;
[0044] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0045] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0046] from Figure 2It can be seen that the first week discharge curve of the sodium ion battery assembled with the prepared NaCrO2 material as the positive electrode material has a discharge capacity of 106.21 mAh / g in the first week, the discharge curve platform is a slope type, and the average voltage is about 3.0V.
[0047] from Figure 3 It can be seen that the peak shape is disordered, the spectrum peak becomes broadened, and the crystallinity is greatly reduced.
[0048] from Figure 4 It can be seen that the charging capacity is as high as 210.37 mAh g -1 It is much higher than conventional sodium-ion battery positive electrode materials and can provide sufficient active sodium ions for the battery system.
[0049] from Figure 5 and Figure 6 It can be seen that the NaCrO2 material prepared in Example 1 is added into the NFPP electrode as a sacrificial salt at a content of 10% (mass percentage), which can reduce the first-week coulombic efficiency from 96.12% to 88.82%. At the same time, the discharge capacity of the material decreases in the same proportion as the amount of sacrificial salt added. At a rate of 0.2C, the first-week discharge capacity of NFPP is 95.30 mAh g -1 NFPP@10%NaCrO2 has a first-week discharge capacity of 89.64 mAh g -1 The capacity retention rates of NFPP and NFPP@10%NaCrO2 after 400 cycles at 2C rate were 101.19% and 100.33%, respectively. The first-week charge-discharge specific capacity, first-week coulombic efficiency, and capacity retention rate after 400 cycles indicated that the addition of 10% NaCrO2 sacrificial salt material did not affect the charge-discharge process of NFPP, but only provided additional active sodium ions to the battery system, making it an ideal sacrificial salt additive.
[0050] Example 3
[0051] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0052] 1. Weigh 0.03 mol sodium oxalate and 0.02 mol sodium chromate;
[0053] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at 60 Hz for 6 h to obtain NaCrO2 material;
[0054] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0055] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0056] Example 4
[0057] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0058] 1. Weigh 0.03 mol sodium oxalate and 0.02 mol sodium chromate;
[0059] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at a frequency of 50 Hz for 7 hours to obtain NaCrO2 material;
[0060] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0061] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0062] Example 5
[0063] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0064] 1. Weigh 0.03 mol sodium oxalate and 0.02 mol sodium chromate;
[0065] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at a frequency of 40 Hz for 6 h to obtain NaCrO2 material;
[0066] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0067] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0068] Example 6
[0069] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0070] 1. Weigh 0.03 mol sodium oxalate and 0.02 mol sodium chromate;
[0071] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at a frequency of 60 Hz for 8 h to obtain NaCrO2 material;
[0072] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0073] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0074] Example 7
[0075] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0076] 1. Weigh 0.02 mol sodium citrate and 0.02 mol sodium chromate;
[0077] 2. The weighed material was transferred into a ball mill and subjected to planetary ball milling at 500 r / min for 6 h to obtain NaCrO2 material;
[0078] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0079] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0080] Example 8
[0081] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0082] 1. Weigh 0.02 mol sodium citrate and 0.02 mol sodium chromate;
[0083] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at a frequency of 60 Hz for 8 h to obtain NaCrO2 material;
[0084] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0085] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0086] Example 9
[0087] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0088] 1. Weigh 0.06 mol sodium gluconate and 0.02 mol sodium chromate;
[0089] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at 60 Hz for 6 h to obtain NaCrO2 material;
[0090] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0091] 4. The prepared Na1CrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0092] Example 10
[0093] This embodiment relates to a method for preparing sodium chromite, a layered oxide material for sodium ion batteries. The preparation and testing steps include:
[0094] 1. Weigh 0.03 mol sodium oxalate and 0.02 mol sodium chromate;
[0095] 2. The weighed material was transferred into a ball mill and subjected to high-energy ball milling at a frequency of 60 Hz for 10 h to obtain NaCrO2 material;
[0096] 3. Prepare the electrode sheet with the prepared NaCrO2 material, PVDF and superconducting carbon black in a mass ratio of 8:1:1, use the metal sodium sheet as the negative electrode, polypropylene as the diaphragm, and the electrolyte system of 1 mol / L LiPF6FEC:DMC=3:7, and assemble the CR2032 button battery in a glove box filled with argon;
[0097] 4. The prepared NaCrO2 material, NFPP (sodium iron pyrophosphate), PVDF, and superconducting carbon black were used in a mass ratio of 1:7:1:1 to prepare the electrode sheet. A metal sodium sheet was used as the negative electrode, polypropylene was used as the diaphragm, and the electrolyte system was 1 mol / L LiPF6FEC:DMC=3:7. CR2032 button batteries were assembled in a glove box filled with argon.
[0098] Table 1
[0099] Used as positive electrode material for sodium battery Used as sodium supplement Discharge capacity mAh / g (2.2~3.6V) Sodium supplement capacity mAh / g (2.2~4.5V) Example 1 106.21 210.37 Example 2 104.32 210.25 Example 3 105.69 208.99 Example 4 89.11 198.10 Example 5 103.99 208.65 Example 6 98.89 189.49 Example 7 104.96 195.98 Example 8 99.33 197.67 Example 9 106.11 183.97 Example 10 95.98 184.22
[0100] Table 1 is a summary table of electrochemical performance data of NaCrO2 materials prepared in various embodiments, which are used as sodium positive electrode materials and sacrificial salt sodium supplement agents respectively. The discharge specific capacity of Examples 1 to 10 used as positive electrode materials is all above 89 mAh / g, and the highest discharge specific capacity is 106.21 mAh / g, which is a relatively ideal positive material for sodium ion batteries, indicating that this scheme can effectively synthesize positive electrode NaCrO2 materials; when used as sodium sacrificial salt sodium supplement agents, the sodium supplement specific capacity of Examples 1 to 10 is all higher than 189 mAh / g, and the highest sodium supplement specific capacity is 210.37 mAh / g, which is much higher than the specific capacity of existing sodium positive electrode materials, and can effectively make up for the loss of active sodium ions in various sodium ion battery systems. The present invention prepares NaCrO2 materials in one step through solid-phase redox reaction. Under different voltage windows, it is not only a high-performance sodium ion battery positive electrode material, but also can be used as a sacrificial salt sodium supplement agent, which has broad application prospects and important commercial value.
[0101] The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.
Claims
1. A method for preparing sodium chromite, a layered oxide material for sodium ion batteries, characterized in that The following steps are involved: The method uses a reducing sodium source and a hexavalent chromium source as raw materials and is directly prepared through a solid phase redox reaction.
2. The method for preparing sodium chromite, a layered oxide material for sodium ion batteries according to claim 1, characterized in that: The molar ratio of the reducing sodium source to the hexavalent chromium source is 0.8 to 1.
2.
3. The method for preparing sodium chromite, a layered oxide material for sodium ion batteries according to claim 1, is characterized in that: The fixed initiation reaction method is one or more of high-energy ball milling, planetary ball milling, sand milling and high-speed stirring and mixing of powders.
4. The method for preparing sodium chromite, a layered oxide material for sodium ion batteries according to claim 1, is characterized in that: The reducing sodium source is one or more of sodium citrate, sodium formate, sodium oxalate, sodium acetate, disodium ethylenediaminetetraacetate, sodium gluconate and sodium hydride.
5. The method for preparing sodium chromite, a layered oxide material for sodium ion batteries according to claim 1, characterized in that: The hexavalent chromium source is one or more of chromium trioxide, chromium peroxide, and sodium chromate.
6. The method for preparing sodium chromite, a layered oxide material for sodium ion batteries according to claim 3, is characterized in that: The mixing equipment tank is equipped with a pressure relief valve during ball milling, sand milling or high-speed stirring.
7. The method for preparing sodium chromite, a layered oxide material for sodium ion batteries according to claim 3, is characterized in that: The ball-to-material ratio of high-energy ball milling or planetary ball milling is 10-30.
8. The method for preparing sodium chromite, a layered oxide material for sodium ion batteries according to claim 3, is characterized in that: The solid phase redox reaction time should be 4 to 10 hours.
Citation Information
Cited By
Core-shell structure sodium ion battery positive electrode material and in-situ coating preparation method thereof
CN121366885A
A core-shell structure sodium ion battery positive electrode material and an in-situ coating preparation method thereof
CN121366885B
Sodium-ion battery positive electrode material with high cycling stability and preparation method of sodium-ion battery positive electrode material
CN121662772A